How do you differentiate #f(x)=ln(6 sin^2(x^3 + 2x))# using the chain rule?

Answer 1

#f'(x)=(6x^2+4)cot(x^3+2x)#

The first issue is the natural logarithm. We can use the chain rule to apply specifically to natural logarithm functions:

#d/dx(ln(x))=1/x" "=>" "d/dx(ln(g(x)))=1/(g(x))*g'(x)#

Applying this to the function at hand, we see that

#f'(x)=1/(6sin^2(x^3+2x))*d/dx(6sin^2(x^3+2x))#

We can simplify this very slightly to avoid length issues:

#f'(x)=(d/dx(6sin^2(x^3+2x)))/(6sin^2(x^3+2x))#

Be careful about the next step. You may be tempted to immediately try to deal with the sine function, but the overriding issue here is the fact that the sine function is squared. Use the chain rule in the case of a squared function:

#d/dx(x^2)=2x" "=>" "d/dx(h(x))^2=2h(x)*h'(x)#

This yields

#f'(x)=(12sin(x^3+2x)*d/dx(sin(x^3+2x)))/(6sin^2(x^3+2x))#

We can take a moment to simplify:

#f'(x)=(2*d/dx(sin(x^3+2x)))/sin(x^3+2x)#

Now, we can differentiate the sine function through the chain rule:

#d/dx(sin(x))=cos(x)" "=>" "d/dx(sin(k(x)))=cos(k(x))*k'(x)#

Applying this allows us to obtain

#f'(x)=(2cos(x^3+2x)*d/dx(x^3+2x))/sin(x^3+2x)#
The calculus gods allow us a moment of respite as we use the power rule to differentiate #x^3+2x#:
#f'(x)=(2(3x^2+2)cos(x^3+2x))/sin(x^3+2x)#
Now, for a tiny bit of simplification we can distribute the #2# into #(3x^2+2)# and recognize the #cos(theta)/sin(theta)=cot(theta)# pattern.
#f'(x)=(6x^2+4)cot(x^3+2x)#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To differentiate (f(x) = \ln(6\sin^2(x^3 + 2x))) using the chain rule, follow these steps:

  1. Identify the inner function: (u = 6\sin^2(x^3 + 2x)).
  2. Differentiate the inner function: (u' = 12\sin(x^3 + 2x)\cos(x^3 + 2x)(3x^2 + 2)).
  3. Apply the chain rule: (f'(x) = \frac{1}{u} \cdot u').
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7